Confronting the ‘Dirty War’ in Argentine Cinema, 1983-1993: Memory and General Historical Representations - Tompkins, Cynthia (Imagofagia, 2021)
Sobre Burucúa Constanza. Confronting the ‘Dirty War’ in Argentine Cinema, 1983-1993: Memory and General Historical Representations. Suffolk, Támesis, 2009. Palabras clave: reseña, Constanza Burucúa, Confronting the ‘Dirty War’ in Argentine Cinema, 1983-1993: Memory and General Historical Representations